Urgensi Penerapan Anggaran Responsif Gender Di Pemerintah Daerah - Paskanova Christi Gainau (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2018)
This study aims to know why gender responsive budgeting is not responsed by local government. Since it was issued by president as we know as Presidential Instruction Number 9 of 2000, there was no any significance changin in gender equality. This research was developed by some previous researches in Indonesia that found many regulations have setted to promote gender equality, but there was no significant action that showed by local government to implement it. So, this study try to seek what the obstacle that hampered gender reponsive budgeting implementation in local government. Documentation study and depth interview were the the tools to capture the data. The research found some obstacles such us the understanding of gender concept among government official, political will, and resistance to change. Some strategies to handle these obstacles are (1) political committment affirmation; (2) technical capacity affirmation; (3) accountability; (4) establish planning and budgeting department; (5) build the network with private sector, academicion, and society empowerment activity group. Contribution of this research include to developed theory in public sector accounting especially in budgeting process, and give understanding about gender responsive budgeting in local government. The last important contribution is to give suggestion and overview for Manado City governement to start gender responsive budgeting implementation.